Fem on Heat and Mass Transfer Flow Through Porous Medıum in a Rectangular Vessel wıth Effect of Thermal Radıatıon and Dıffusıon - Satish Molli, T. Siva Nageswara Rao, V. Venkateswara Rao (International Journal of Advanced Science and Technology, 2020)
The present article deal with deportation Calidity and conglomeration transposition flow over a permeable passable in a rectangular duct with effects of gratification effects , chemical reaction and radiation. With the help of finite element analysis(Galerkin method) with three nodded triangle elements we solved governing equations of flow heat and mass transfer. The ratio of momentum diffusivity P is taken to be 0.71. In this analysis we found the change in Sherwood number and Nusselt number (Nu) with respect to different parameters. In view of different parameters like Soret effect and radiation effect on non dimensional temperature, concentration has been discussed. This numerical results shown two different fluid flow systems related to the ratio of external Raleigh numbers together with the internal energy. Also, it was found that along the cold wall increased with higher external Rayleigh numbers and lowering with internal Rayleigh numbers. The Literature advocates that the variation of viscous dissipation with different geometries on heat transfer as been studied. By finite element analysis we analyses the mass and heat transfer in Porous Rectangular Cavity wit different parameters at side walls. Also we observed the thermal radiation acts convincing part in comprehensive surface fieriness displacement with lowering in heat transfer. Keywords: Mass and Heat transfer, Rectangular duct, Chemical reaction, radiation, dissipation